The price of collaboration: How authoritarian states retain control - Piotrowska, B (SAGE Publications, 2020)
How does access to foreign or independent media affect the operation of a state security apparatus? This paper answers this question concentrating on two characteristics of the informant network of the East German Stasi: the number of informants and their “price”. Exposure to West German TV (WGTV) had the potential to decrease the supply of informants and increase the demand for them, pushing up the value of the payments the informants received, but leaving their quantity theoretically ambiguous. I verify this reasoning using a rare original dataset of Stasi informants. Results show that informants were given approximately 70 East German marks worth of rewards more per year in the areas that had access to WGTV, as compared to areas with no reception – ironically an amount roughly equivalent to the cost of an annual East German TV subscription. These findings demonstrate how an authoritarian state can counteract the potentially destabilizing effect of foreign media.